Implementation of restaurant location searching Geographic Information Systems using Android-based local based services method - Raja Nasrul Fuad; Hafni Hafni; Fadli Pratama (Brilliance: Research of Artificial Intelligence, 2021)
Finding a restaurant location as a place to enjoy food becomes something that is very inconvenient, especially for tourists or food connoisseurs who are not familiar with the area. It takes several tools, especially the use of Android-based smartphones as an operating system that is very popular with the public lately. This research is expected to make it easier for users to find food in restaurants that users want. The use of this system is divided into two, namely admin and user (general users). This system is integrated with the existing GPS on the smartphone. This application also shows the distance traveled and time traveled by motorbike or car to the location and displays an estimate if using public transportation.